KARAKTER WARGA NEGARA YANG BAIK DAN CERDAS - ., Winarno (PKn Progresif, 2012)
This paper will reveal the terms of the good citizens and intelligent, also distinguish the good and intelligent (smart and good man). Furthermore, we will make comments about a teacher of character